EVALUASI PENGELOLAAN KUALITAS AIR BERDASARKAN PARAMETER PH, SUHU, DAN DISSOLVED OXYGEN PADA BUDIDAYA IKAN KERAPU DI BBPBL LAMPUNG - Aulia Cantika; Finda Hasna Azizah; Antika Sari; Sumardi; Berti Yolida; Nadya Meriza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Water quality is one of the key factors determining the success of grouper aquaculture because it affects the growth, health, and survival of the fish. Proper water quality management requires monitoring important parameters, such as temperature, pH, and dissolved oxygen (DO), to ensure that water conditions remain within a range suitable for the biological needs of the fish. This study aims to evaluate water quality management based on pH, temperature, and dissolved oxygen (DO) parameters in grouper aquaculture at the Lampung Marine Aquaculture Research and Development Center (BBPBL). The study employed a descriptive method with a qualitative approach. Data were collected through semi-structured interviews with managers, direct observations during site visits, documentation of water quality monitoring results obtained from the Lampung Marine Aquaculture Center (BBPBL), and a literature review. The data were analyzed descriptively by comparing the results of water quality management against the recommended parameter ranges cited in various scientific literature. The results of the study indicate that water quality management at the Lampung BBPBL is carried out through routine monitoring of temperature, pH, and dissolved oxygen parameters as an effort to maintain optimal aquaculture environmental conditions. Based on the evaluation results, water quality management has been implemented in accordance with the needs of grouper aquaculture, thereby supporting environmental conditions conducive to fish growth and survival. Therefore, periodic monitoring and management of water quality must be maintained as part of efforts to improve the effectiveness of grouper aquaculture.